2023
DOI: 10.1007/s12020-023-03478-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of dietary fiber on preventing gestational diabetes mellitus in an at-risk group of high triglyceride-glucose index women: a randomized controlled trial

Yannan Cao,
Jing Sheng,
Dongyao Zhang
et al.

Abstract: BackgroundPregnant women with a high triglyceride-glucose (TyG) index during early pregnancy may increase the risk of gestational diabetes mellitus (GDM), and dietary ber could play an important role in glucose and lipid metabolism. However, no trials have tested the effects of dietary ber on preventing GDM in women with a high TyG index. This study aims to investigate whether GDM can be prevented by dietary ber supplementation in women with a TyG index ≥ 8.5 during early pregnancy (< 20 weeks). MethodsA rando… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, no effect on the lipid profile was observed [ 49 ]. In another study from 2023, it was observed that dietary fiber supplementation (24 g of dietary fiber powder/day) during pregnancy may prevent gestational diabetes mellitus and preterm birth in women before 20 weeks of gestation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no effect on the lipid profile was observed [ 49 ]. In another study from 2023, it was observed that dietary fiber supplementation (24 g of dietary fiber powder/day) during pregnancy may prevent gestational diabetes mellitus and preterm birth in women before 20 weeks of gestation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle modifications such as diet and physical activity can reduce gestational weight gain and may even reduce postnatal weight retention, GDM, hypertension, cesarean section, preeclampsia, and preterm birth [43]. Women with a high triglyceride-glucose index may be at increased risk for developing GDM; dietary fibers can reduce the risk of GDM significantly, decrease preterm birth, and significantly increase gestational age [44]. Smoking is associated with adverse neonatal outcomes; when compared with women who stopped smoking during pregnancy, women who continued smoking had a significantly higher risk of low birth weight and preterm birth (aOR=1.31) [45].…”
Section: Diabetes Mellitus and Lifestylementioning
confidence: 99%
“…Dietary macronutrients have also been linked to increasing GDM risk including the consumption of low fiber, high glycemic index diets [12] and low carbohydrate, high-fat diets [13]. Of late a whole host of dietary strategies have been or are being studied to investigate potential links with alterations in GDM risk, including variations of the Mediterraneanstyle diet [14,15], high-fiber diets [16], diets with high complex carbohydrate contents [17], plant-based dietary patterns [18], diets high in probiotic yogurt contents [19], and diets with high colorful fruit and vegetable contents [20]. Further, observational dietary studies have reported associations between GDM risk and protein intake in early pregnancy (higher risk with increased early animal protein intakes and lower risk with increased early plant protein intakes [21]).…”
mentioning
confidence: 99%